Kemampuan Memahami Makna Konsep Kosakata Bidang Ilmu Bahasa Indonesia, Matematika, Seni Budaya dan Prakarya (SBdP), dan Pendidikan Kewarganegaraan Siswa Kelas III Sekolah Dasar - Metroyadi Metroyadi; Wahdah Refia Rafianti; Rizky Amelia (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This study aims to reveal students' abilities in understanding vocabulary in the fields of Indonesian, Mathematics, Arts, Cultural, and Crafts (SBDP), and Citizenship Education. This type of research is descriptive quantitative. The population was all grade 3 students in Kecamatan Banjarmasin Utara who lived in 41 elementary schools. Samples were taken based on probability sampling. The results showed that the comparison of learning outcomes between the groups was as follows: (1) there is one cluster for PPKN, Mathematics, Indonesian and SBDP subjects, (2) there are different PPKN learning outcomes and there is also that is not different, (3) PPKN learning outcomes between other groups are not significantly different, (4) Mathematics learning outcomes are significantly different and some are not different, (5) Indonesian learning outcomes are significantly different and there are also not different, (6) the SBDP learning outcomes between groups were significantly different and some were not.